The well-being and social value of playing soccer for men and women - Paul Downward; Pamela Wicker; Tim Thorman (2024)
This study examines the well-being and social value of playing different forms of soccer for men and women by employing the compensating variation approach to survey data from eight European countries. Framed by the desired objective of Title IX, this research assesses possible gender differences in the social benefits of sport. Social values exceed those of individual well-being derived from playing soccer, with the values of both being greater for women. Less formal forms of soccer yield generally higher monetary values than the competitive 11-a-side format. As the marginal returns are greater, investment should promote women’s engagement and more informal playing opportunities.